Pengaruh PDRB, Kemiskinan, dan Jumlah Penduduk Terhadap IPM di Provinsi Jawa Timur Tahun 2017-2021 - Yuni Rinawati; Firda Aulia Nur Miftitah; Fahmi Alif Aldianto; Muhammad Hafidz Faj'ri; Agus Eko Sujianto (Universitas Negeri Padang, 2022)
The purpose of this study is to analyze the effect of GRDP, poverty, and population on HDI in East Java Province in 2017-2021 both partially and simultaneously. This study uses a quantitative method with panel data regression using the Eviews 10 program. In interpreting the data using the Fixed Effect Model (FEM). The F-test shows that GRDP, poverty and population have a significant effect on HDI. Whereas in the t-test, GRDP has a positive and significant effect on HDI, poverty has a negative and significant effect on HDI, population size has a positive and significant effect on HDI. The results of these findings imply that it is important to pay attention to and strive for an increase in GRDP, the role of the government in poverty alleviation must also be continuously pursued and improved because these two things contribute to increasing the HDI. In addition, the government also needs to pay attention to the large population that needs to be balanced with employment because the number of people absorbed as labor will get income that can be used to improve the quality of life of the population.